REFORMING THE GOVERNMENT ACCOUNTING SYSTEM IN IRAQ IN ACCORDANCE WITH INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARDS - Iman Shakir Mohammed (Scholars Digest Publishing, 2024)
This research aims to demonstrate the possibility of applying the International Public Sector Accounting Standards (IPSAS) in reforming the governmental accounting system in Iraq by adopting a modified model based on the standard model presented by (Hughes, 2013) and proposed by the International Federation of Accountants. Due to the Iraqi specificity situation, the modified model includes seven stages instead of six stages presented by Hughes, 2013 by adding a capacity building stage (training at all stages). Researcher believes that adding this stage is important because the Iraqi public sector accounting system in its current situation is not ready to apply the international standers, so this stage will pave the way for implementation of the international standards. It is known that the importance of developing the system as to be a main source of the necessary governmental financial data to improve governmental performance and preserve public money. The research concluded that adopting IPSAS standards in Iraq will help the governmental accounting system achieve transparency, accountability, and reliability in governmental financial information. The proposed model can be adapted to suit the Iraqi environment after adding the seventh stage, which is the capacity building stage to ensure proper implementation. To confirm the suitability of our modified proposed model with the Iraqi public accounting system an exploratory study has been done. In the exploratory study, the research sample includes 80 highly experienced specialists in the Iraqi public accounting sector. Statistical analysis of the study data show a clear indication that the modified model was correct and appropriate to Iraqi environment especially the direction of opinion (strongly agree) for the modified stage, capacity building stage (training at all stages) with a high value of arithmetic average.
Keywords: government accounting system; IPSAS; public sector; reforming